The Role of the Serdang Bedagai Government's Communication and Information Service (Diskominfo) in the Development of the Bah Bolon White Water Rafting Tourist Attraction - Putri, Alvi Zakiyah; Zuhriah, Zuhriah (IHSA Institute, 2024)
The concept of role refers to what individuals do within society as part of an organization. Information dissemination is a key aspect of the Communications and Informatics Service's role in fulfilling its duties. This research aims to examine the role of the Serdang Bedagai Government Communications and Informatics Service in developing the Bah Bolon White Water Rafting tourist attraction. Using a qualitative descriptive method with in-depth interviews and observations, the study explores how regional governments act as motivators, facilitators, and dynamists in tourism development. The Serdang Bedagai Communications and Informatics Service has made efforts to enhance its function in promoting and advancing the Bah Bolon White Water Rafting attraction